Artificial Intelligence in English Language Learning: A Systematic Review of AI Tools, Applications, and Pedagogical Outcomes - Kristiawan, Dana; Bashar, Khaliq; Pradana, Dian Arief (The Art of Teaching English as a Foreign Language (TATEFL), 2024)
This systematic review examines the role of artificial intelligence (AI) in English language teaching (ELT), analyzing AI tools, applications, and their pedagogical outcomes. AI technologies, such as chatbots, intelligent tutoring systems, and speech recognition software, are increasingly used to enhance language learning experiences. The review follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) model, a standardized approach that ensures transparency and rigor in identifying, screening, and analyzing relevant literature. PRISMA emphasizes clear documentation of the selection process, including inclusion and exclusion criteria, to provide a systematic and replicable methodology for comprehensive reviews. Through thematic qualitative analysis of recent literature indexed in Scopus and Web of Science, key themes emerged regarding AI types, applications, teacher and learner perspectives, and ethical considerations. Findings reveal that AI tools enhance learner engagement, provide personalized learning experiences, and improve language proficiency, particularly in speaking and writing. However, challenges remain, such as accessibility barriers, teacher preparedness, and ethical concerns around data privacy and bias. This review proposes a framework for AI integration in ELT, focusing on access, teacher training, ethical standards, and blended learning models to optimize AI’s benefits. The study underscores the need for targeted teacher training and ethical standards to maximize AI’s effectiveness and sustainability in ELT. This framework and the review findings aim to support educators, developers, and policymakers in fostering an AI-enriched learning environment that aligns with educational goals while addressing existing limitations.